Mechanisms behind zinc transport in a calcareous soil-wheat system and their impacts on human health - Su-rong Zhang; Jun-quan Yang; Da-ming Wang; Xue-sheng Gao; Ji-hong Liu; Jing Zhang; Xiao-long Duan; Jian-hua Wang; Ling-zhi Yang (China Geology, 2025)
ABSTRACT: Zinc is recognized as a vital biological element for animals and plants. Both zinc deficiency and excess will cause damage to cells, and zinc deficiency in the human body may lead to severe health problems. Zinc deficiency has been identified as a global nutritional issue. Wheat, one of the most significant food crops for humans, is primarily planted in potentially zinc-deficient, calcareous soils in China. It proves to be a major global challenge to increase the zinc concentration in wheat crops to boost crop yields and improve human health. This study investigated the growth process of wheat in calcareous soils with various zinc concentrations using outdoor pot experiments and systematically explored the characteristics and mechanism of zinc transport in the soil-wheat system. The results indicate that the zinc concentrations in various wheat organs decreased in the order of roots, stems, and leaves in the jointing stage and in the order of seeds, roots, and stems in the mature stage. Overall, the zinc enrichment in various wheat organs decreased in the order of seeds, roots, stems, and leaves. In the case of zinc deficiency in soils, wheat roots exhibited elevated zinc availability in the rhizosphere by secreting phytosiderophores. This enhances the zinc uptake capacity of wheat roots. In the case of sufficient zinc supply from soils, chelated zinc formed with citric acid as the chelating ligand occurred stably in soils, contributing to enhanced utilization and uptake rates of zinc, along with elevated transport and enrichment capacities of zinc inside the plants. The results indicate that the zinc concentration in wheat seeds can be somewhat enhanced by regulating the background value of bioavailable zinc concentration in soils. A moderate zinc concentration gradient of 1.0 mg/kg is unfavorable for zinc accumulation in wheat seeds, while a high zinc concentration gradient of 6.0 mg/kg corresponds to the highest degree of zinc enrichment in wheat seeds. This study holds critical scientific significance for enhancing the zinc supply capacity of soils, increasing the zinc concentrations in wheat seeds, and, accordingly, addressing zinc deficiency in the human body. Additionally, this study offers a mechanistic reference and basis for research on the interplay between soils, plants, and human health.